Toothbrushing and flossing habits in young adults : a video-based observational study - Winterfeld, Tobias Max; Justus Liebig University Giessen (My University, 2014)
The present descriptive, cross-sectional and non-disguised observational study was conducted to observe and perform a computerised analysis of the everyday toothbrushing and, for the first time, flossing habits of adolescents, who have recently reached the age of legal majority. At this age, the legally anchored prevention programme ends, and no further systematic toothbrushing assistance is provided. Therefore, 101 inhabitants of Giessen aged between 18-19 years were included. After the plaque index was assessed according to Silness and Loe, the participants were filmed while performing their habitual toothbrushing and flossing in the dental clinic in Giessen (Germany). All the participants were aware of the filming. Subsequently, they completed questionnaires to provide their socio-demographic data and some psychological data. The video analysis was performed with the observation software INTERACT 9. Different toothbrushing parameters, as described in literature from the seventies, were assessed, such as brushing duration, brushing movements, starting location, the frequency of alternations between areas of the mouth and flossing technique. This study showed that the participants brushing duration corresponded to the international recommendations; however, only a few of the participants exhibited a systematic brushing technique. The motion sequences during toothbrushing were characterised by frequent changes between the anterior and posterior areas. The brushing movements of most of the participants were characterised by elements that were taught as a part of oral hygiene education in kindergarten and primary school. Many participants did not reach all the areas, especially the oral surfaces of the posterior teeth. An interesting finding is that similar toothbrushing motion sequences performed by adolescents were observed in the late seventies. These sequences included the preferred brushing of vestibular surfaces, the neglect of brushing the oral surfaces and the tendency towards frequent alternations from the anterior vestibular to the posterior vestibular areas, and vice versa. Flossing was performed by almost half of the participants, whereas a discrepancy between the self-reported and actual flossing was recognised. Five of them reached all the interproximal spaces; only two performed a correct flossing technique, and just one flossed correctly and completely. In conclusion, there was a general deficiency in flossing abilities. For the first time, the new method used in the present work allowed the visualisation of brushing patterns, which led to a characterisation of three different toothbrushing types: systematic, sequential and unstructured movement patterns. It is conceivable that these patterns represent different predictors for the success of oral hygiene instructions. The present results show a discrepancy between the efforts of prevention strategies regarding oral hygiene education and the actual, observed oral hygiene habits in young adults. Strategies for imparting oral hygiene techniques, especially within individual prophylaxis, should be reconsidered. The complexity of this task requires an interdisciplinary approach. The present method for analysing toothbrushing behaviour offers the possibility of differentially and objectively observing and evaluating motion sequences over a number of sessions. This possibility offers the opportunity to answer multi-layered questions concerning, for example, the persistence of movement patterns and their relevance for instruction strategies, to investigate the age- and development-associated learnability of brushing techniques for children, the motor aspects of oral hygiene of older people or oral hygiene training for people with cognitive or motor handicaps.

Das Ziel der vorliegenden deskriptiven, nicht verblindeten Querschnittsstudie war es, das habituelle Zahnputzverhalten und, zum ersten Mal, die Anwendung von Zahnseide bei jungen Erwachsenen am Ende der gesetzliche geregelten Prophylaxeunterstützung videobasiert und computergestützt zu analysieren. Hierfür wurden 101 Einwohner aus Gießen im Alter zwischen 18 und 19 Jahren untersucht.Nachdem der Plaque Index nach Silness und Löe erhoben wurde, wurden die Probanden während der Durchführung ihres habituellen Putzvorgangs in der Zahnklinik in Gießen gefilmt. Alle Probanden wussten, dass sie gefilmt werden. Zum Schluss beantworteten sie soziodemographische und psychologische Fragebögen.Die Videoanalyse wurde mit der Beobachtungssoftware INTERACT 9 durchgeführt. Verschiedene Zahnputzparameter die bereits in der Literatur in den späten siebziger Jahren beschrieben wurden, wie die Putzdauer, die Bürstbewegungen, die Startregion, die Häufigkeit der Wechsel zwischen den Mundarealen und die Zahnseidentechnik wurden erhoben.Die Ergebnisse der Studie zeigten, dass die meisten Probanden, entsprechend den aktuellen internationalen Empfehlungen, lange genug putzten, allerdings nur wenige eine systematische Putztechnik erkennen ließen. Die Bewegungsabläufe waren durch häufige Wechsel zwischen den anterioren und posterioren Arealen geprägt. Die Putzbewegungen der meisten Probanden beinhalteten Elemente, die im Rahmen der Mundhygieneerziehung im Kindergarten und in der ersten und zweiten Klasse in Grundschulen vermittelt werden. Viele Probanden erreichten nicht alle Areale vor allem nicht die oralen Flächen der Seitenzähne. Interessant ist, dass vergleichbare Bewegungsabfolgen mit der Zahnbürste bei jungen Erwachsenen bereits Ende der siebziger Jahre beobachtet wurden. Darunter fallen die Bevorzugung der vestibulären Flächen, Vernachlässigung des Putzens der oralen Flächen und die häufigen Wechsel von den anterioren Regionen zur linken und rechten Seite und umgekehrt.Nur die Hälfte der Probanden verwendete Zahnseide, wobei eine Diskrepanz zwischen berichtetem und beobachtetem Verhalten zu verzeichnen war. Fünf Probanden erreichten alle Interdentalräume, lediglich zwei zeigten die richtige Technik und nur einer von diesen zeigte die richtige Technik und erreichte alle Interdentalräume. Zusammenfassend ist festzustellen, dass ein generelles Defizit bei der Verwendung von Zahnseide zu beobachten war.Zum ersten Mal konnte durch die im Rahmen dieser Arbeit neu entwickelte Methodik zur Visualisierung der Zahnputzabläufe eine Charakterisierung in drei verschiedene Putztypen vorgenommen werden: systematische, sequentielle und ungeordnete Bewegungsmuster. Es ist denkbar, dass diese womöglich Prädiktoren für eine erfolgreiche Mundhygieneerziehung darstellen.Die vorliegenden Ergebnisse zeigen, dass die Ziele in Bezug auf die Mundhygieneerziehung der Gruppen- und vor allem der Individualprophylaxe bisher unvollständig erreicht wurden. Die Strategien für die Vermittlung von Mundhygienetechniken, speziell im Rahmen der Individualprophylaxe, sollten überdacht werden. Aufgrund der Komplexität dieser Aufgabe ist dazu ein interdisziplinärer Ansatz zu fordern.Die vorgestellte Methode zur Videoanalyse bietet erstmals die Möglichkeit, Bewegungsabläufe über mehrere Sitzungen differenziert und objektivierbar zu beobachten und auszuwerten. Damit eröffnet sich der Ausblick auf die Beantwortung vielschichtiger Fragestellungen, beispielsweise zu der Persistenz von Bewegungsmustern und deren Relevanz für Instruktionsstrategien, Untersuchungen zu alters- und entwicklungsabhängiger Erlernbarkeit von Putztechniken bei Kindern, motologische Aspekte der Mundhygiene älterer Menschen oder Mundhygienetraining bei Personen mit motorischen oder kognitiven Einschränkungen.
Zahnputzgewohnheiten junger Erwachsener : eine videobasierte Beobachtungsstudie über die Anwendung von Zahnbürste und Zahnseide
Keywords: ddc:610